Estilos de aprendizaje y hábitos de estudio en alumnos del nivel secundario Colegio Experimental UNAP San Juan Bautista 2023 - Zambrano Vela, Cristina Abigael (2025)
The purpose of the research carried out at the UNAP San Juan Bautista Experimental School during the year 2023 was to explore the relationship between the learning styles and study habits of high school students. Using a confirmatory approach, a field, cross-sectional and correlational study was carried out. To this end, two surveys were administered to a representative group of 218 students, chosen through a proportional and random selection method. The analysis carried out using Spearman's correlation coefficient indicated a strong positive relationship between learning styles and study habits, with a coefficient of 0.781 and a significance level below 0.05. This result is solid support for the hypothesis proposed in the study and verifies the achievement of its main objective. The analysis carried out using Spearman's Rho test revealed a statistically significant relationship between the learning styles - active, reflective, theoretical and pragmatic - and the study habits of the students in the study sample. With correlation coefficients ranging between 0.591 and 0.710, these data support the hypotheses raised in the study, confirming its scientific validity.